ANALISI PENETAPAN WILAYAH PEMBANGUNAN DI KABUPATEN SAMOSIR - Renhard Gultom; R. Mulyo Hendarto (Diponegoro Journal of Economics, 2014)
ABSTRACT      Samosir Regency is the one of regency which has seperated from Toba Samosir Regency. As a new regency, Samosir must be need a structural, relevant, and efficient development plan. Determining Development Area Unit is the one of theoretical and practical concept which can be referenced in order to make development policy      There are several aims of this research. They were to find out the economical basics and potencies in Samosir Regency, to find out the economical potencies from every subdistricts in Samosir, to find out which subdistricts that can be a growth pole in Samosir, to find out the interactional strength among the districts, and to design a Development Areal Units in Samosir Regency. To reach that aims, this study use Location Quotient, Shift-share analysis, indirect method, Gravitation Analysi, and Scalogram. The data that used in this study are province’s GDP, regency’s GDP, population quantities, distances among the district’s capital and the quantities and type of services facilities available in each subdistrict in Samosir Regency.      The result of the analysis showed that there were 3 Development Area Units that is identified in Samosir Regency. They were Development Area Unit I (DAU I) including Pangururan, Sianjurmulamula, Harian and Ronggurnihuta subdistricts, Development Area Unit II (DAU II) including Simanindo subdistrict, Development Area Unit III (DAU III) including Nainggolan, Palipi, Onanrunggu and Sitiotio subdistrict.